2017
DOI: 10.2196/resprot.7767
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Delivered Dialectical Behavioral Therapy Skills Training for Suicidal and Heavy Episodic Drinkers: Protocol and Preliminary Results of a Randomized Controlled Trial

Abstract: BackgroundThe need to develop effective and accessible interventions for suicidal individuals engaging in heavy episodic drinking (HED) cannot be understated. While the link between alcohol use and suicidality is a complex one that remains to be elucidated, emotion dysregulation may play a key role in alcohol-related suicide risk in these individuals.ObjectiveIn the current study, an 8-week Internet-delivered dialectical behavior therapy (DBT) skills training intervention was developed and preliminarily evalua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 55 publications
2
13
0
1
Order By: Relevance
“…A growing number of studies have examined this question with some studies finding that telepsychology is effective and equivalent to services delivered FTF, whereas other studies have found mixed results (Turgoose et al, 2018 [videoconferencing and phone]). Telepsychology has generally been found to be an effective treatment delivery method for common mental health conditions experienced by veterans (Bolton & Dorstyn, 2015 [videoconferencing]; Turgoose et al, 2018 [videoconferencing and phone]) including the following: PTSD and other trauma and stressor-related disorders (Wierwille et al, 2016 [videoconferencing]), anxiety (Burke et al, 2019 [internet-delivered]; Yuen et al, 2013 [videoconferencing]), depression (Sztein et al, 2018 [internet-only]), intermittent explosive disorder (Osma et al, 2016 [videoconferencing]), substance use disorders (Wilks et al, 2017 [internet-only]), etc.…”
Section: Effectiveness Of Telepsychologymentioning
confidence: 99%
“…A growing number of studies have examined this question with some studies finding that telepsychology is effective and equivalent to services delivered FTF, whereas other studies have found mixed results (Turgoose et al, 2018 [videoconferencing and phone]). Telepsychology has generally been found to be an effective treatment delivery method for common mental health conditions experienced by veterans (Bolton & Dorstyn, 2015 [videoconferencing]; Turgoose et al, 2018 [videoconferencing and phone]) including the following: PTSD and other trauma and stressor-related disorders (Wierwille et al, 2016 [videoconferencing]), anxiety (Burke et al, 2019 [internet-delivered]; Yuen et al, 2013 [videoconferencing]), depression (Sztein et al, 2018 [internet-only]), intermittent explosive disorder (Osma et al, 2016 [videoconferencing]), substance use disorders (Wilks et al, 2017 [internet-only]), etc.…”
Section: Effectiveness Of Telepsychologymentioning
confidence: 99%
“…After each skill was introduced, they were presented with key points, followed by computer guided practice, and the selection of homework tasks. Participants were sent their chosen homework assignments by email and sent encouraging text messages or emails each day (Wilks et al 2017(Wilks et al , 2018. Wilks et al (2020;p.…”
Section: How Dbt Has Been Operationalized In An Online Environmentmentioning
confidence: 99%
“…The earliest reported trial of a therapist guided DBT intervention was a pilot study by Wilks et al (2017;Wilks et al 2018). Participants with a history of binge drinking in the past month, and with high score on the brief version of the Difficulties in Emotion Regulation Scale (DERS) (Bjureberg et al 2016) were recruited via advertisement into an 8-week therapist assisted online skills group or a waitlist control group.…”
Section: The Effectiveness Of Online Dbtmentioning
confidence: 99%
“…Yet, there has been limited research on the provision of DBT via telehealth. An 8-week form of internet-delivered skills training (iDBT-ST) delivered via videos and interactive tools instead of involving real-time communication with a provider delivering the skills in an interactive way ( Wilks et al, 2017 , Wilks et al, 2018 ) showed promise in reducing suicidal ideation, alcohol consumption, and emotion dysregulation. However, this relatively new intervention is not yet widely used by DBT providers ( Lungu et al, 2019 ) and, further, is not meant to encompass the full model of DBT.…”
mentioning
confidence: 99%